Is It Necessary to Add the Feedback Insufflation Time in Manikins? A Simulation Pilot Study - Luis Castro-Alonso; Eloy Carracedo-Rodríguez; Martín Otero-Agra; Sheila Vázquez-Álvarez; Roberto Barcala-Furelos; María Fernández-Méndez (Reports)
(1) Objective: This study aimed to assess the evolution of the quality of ventilations of a group of rescuers after two training sessions by taking into account inspiration times. (2) Materials and Methods: A pilot simulation study was carried out with a sample of 10 lifeguard students. Two training sessions were held three weeks apart, in which CPR skills were trained by means of feedback tools. Participants performed three tests in pairs on a ResusciAnne QCPR® manikin connected to SkillReporter QCPR software, namely one pre-training test and one test after each training session. CPR was performed in pairs for two minutes and began with five rescue breaths. (3) Results: One training session was enough to improve chest compression quality (T0: 48%; IQR 17–77/T1: 83%; IQR 59–88; p = 0.022/T2: 79%; IQR 64–92; p = 0.002). The quality of the ventilations increased progressively in each training session without reaching high-quality results (T0: 0%; IQR 0–0/T2: 15%; IQR 8–27; p = 0.011). (4) Conclusion: A two-session training program focused on inspiratory times achieved significant improvements in the quality of bag-mask ventilations performed by lifeguard students. Training focused on the insufflation time of ventilations and not only on the volume seems to be an important factor in improving the quality of ventilations.